Author Correction: Metabolic Biomarkers for Prognostic Prediction of Pre-diabetes: results from a longitudinal cohort study. Issue 1 (December 2017) - Zeng, Hailuan; Tong, Renchao; Tong, Wenxin; Yang, Qiaoling; Qiu, Miaoyan; Xiong, Aizhen; Sun, Siming; Ding, Lili; Zhang, Hongli; Yang, Li; Tian, Jingyan
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.